(y+1)2= 4. The power of two becomes a square root on the other side. Don't forget that this is plus or minus the square root of 4. Now we have y+1 = +- sqrt(4). We now have two equations to solve for y. y+1 = 2 or y+1=-2. Giving y = 1 or y = -3.
One to one online tution can be a great way to brush up on your Maths knowledge.
Have a Free Meeting with one of our hand picked tutors from the UK’s top universities
Answered by Benjamin G.
Answered by Edward G.
Answered by Elizabeth W.
Answered by Anna B.